The Analysis Of Test Instrument And The Leaners’ Responses On Acidity Material With The Uses From Environment As The Learning Source - Riyanti Riyanti; Edy Cahyono; Sri Haryani; Budi Naini Mindyarto (International Conference on Science, Education, and Technology, 2022)
This research analyzes the test instrument and the learners' responses to acidity material using an environment as the learning source. This quantitative research collected the data with observation, tests, and questionnaires. The researchers used valid and reliable measuring tools to find out the learning achievements of some aspects. The experts’ judgments involved six experts and question item analyses with classical test theory (CTT) assisted by SPSS 21. The researchers conducted the trial run test and collected the learners’ responses in XI IPA1 of Public SHS 1 Bangsri Jepara, consisting of 35 learners. The data analysis used V Aiken which consisted of question items and learners’ responses. The results were 0.91 and 0.91. The content validity consisted of 40 objective question items in the test material about acidity. The reliability was observable from Cronbach's Alpha score, 0.945. The results indicated the question items were reliable and valid. The test analysis results of acidity material included validity and reliability. The analysis was useful to ensure that the instrument would be suitable for learners with various skills. The researchers also found positive responses toward the learning.